Copper(II) biocompatible coordination solids as potential platforms for diclofenac delivery systems - Alves, Renata Carolina [UNESP]; Lucena, Guilherme Nunes [UNESP]; de Farias, Renan Lira [UNESP]; da Silva, Patrícia Bento [UNESP]; da Silva, Isabel Cristiane [UNESP]; Pavan, Fernando Rogério [UNESP]; Chorilli, Marlus [UNESP]; da Costa Ferreira, Ana Maria; Galvão Frem, Regina Célia [UNESP] (Elsevier, 2020)
This study deals a new copper(II)-based cluster-organic framework, CUBA, targeted a matrix for diclofenac sodium delivery. CUBA was prepared by solvothermal reaction and characterized by several techniques. FEG-SEM data revealed presence of random porous over CUBA surface. BET equation fitting N2-adsorption isotherm showed a surface area and pore volume amount to ca. 55 ​m2 ​g-1 and 0.49 ​cm3 ​g-1, respectively. In vitro assays showed non-cytotoxic activity for CUBA in MRC-5 ​cell line. A microporous copper(II)-based metal-organic framework, herein labelled as BioMOF-Cu, was used as a comparison in drug load-releasing tests. CUBA exhibited encapsulation efficiency of 29.47, 36.74 and 60.72% at 2, 4 and 7 days, respectively, BioMOF-Cu showed 84.68% at 4 days. In PBS solution CUBA ranged at 13-18% of total drug-releasing at 72 ​h and BioMOF-Cu afforded 21% at 48 ​h. In vivo evaluation of the anti-inflammatory effects, CUBA and BioMOF-Cu decreased the paw edema when compared to the negative group.
Keywords: Cluster-organic framework; Diclofenac sodium; Drug delivery; In vivo evaluation